Association of physical activity, sedentary behaviour, sleep and myopia in children and adolescents: a systematic review and dose-response meta-analysis - Huimin Ding; Liqun Jiang; Xuanqiao Lin; Chaoying Ye; Buongo Chun (BMC Public Health)
Abstract Purpose This study aimed to systematically evaluate the dose-response relationships between physical activity (PA), sedentary behavior(SB) (including near work [NW] and screen time [ST]), sleep duration (SD), and myopia risk among children and adolescents. Design Systematic review and dose-response meta-analysis. Methods We systematically searched PubMed, EMBASE, Cochrane Library, and Web of Science up to November 19, 2024. Methodological quality was assessed using Joanna Briggs Institute (JBI) and ROBINS-I tools. Random-effects meta-analyses were used to estimate categorical and continuous dose-response relationships. Subgroup analyses and sensitivity analyses were performed to explore heterogeneity sources and test robustness. Results A total of 45 observational studies (766,848 participants aged 5–19 years) were included. Categorical analyses showed that, compared with the lowest exposure categories, higher PA levels (highest: OR = 0.77, 95% CI: 0.63–0.96; intermediate: OR = 0.76, 95% CI: 0.63–0.93) and longer SD (highest: OR = 0.67, 95% CI: 0.48–0.92; intermediate: OR = 0.82, 95% CI: 0.73–0.92) significantly reduced myopia risk. Conversely, higher levels of NW (highest: OR = 1.71, 95% CI: 1.28–2.27; intermediate: OR = 1.34, 95% CI: 1.19–1.50) and ST (highest: OR = 1.59, 95% CI: 1.14–2.22; intermediate: OR = 1.29, 95% CI: 1.12–1.49) were associated with significantly increased risk. In the continuous dose-response meta-analysis, a linear association was observed between PA, ST, and myopia. Each additional hour of PA per day reduced the risk of myopia by 12%, while each additional hour of ST increased the risk by 31%. Nonlinear associations were found between NW, SD, and myopia. Among children and adolescents, 1.5 and 2.5 h/day of NW increased the risk of myopia by 25% and 29%, respectively. Although longer SD was associated with a reduced risk of myopia, this effect did not reach statistical significance at any exposure level.Subgroup analyses revealed that protective effects of PA were more evident in low- and middle-income countries, smaller sample sizes, and cross-sectional studies, while increased risks related to ST and NW were stronger in low-income settings. No subgroup significantly modified the association between SD and myopia risk. Conclusion Increasing PA, while limiting ST and NW, effectively reduces the risk of myopia among children and adolescents. The association between sleep duration and myopia remains inconclusive, warranting further investigation.